ANALISIS KELAYAKAN INVESTASI PERKEBUNAN RAKYAT KELAPA SAWIT DENGAN SISTEM BAGI HASIL DI DESA BUDI ASIH, KECAMATAN PULAU RIMAU, KABUPATEN BANYUASIN, SUMATERA SELATAN - Demiyati, Trisna; Priatna, Wahyu Budi (Forum Agribisnis, 2013)
One of the efforts made in optimizing the potential of Indonesia is the expansion of plantation estate by the government and the public, either in the form of country estates (PBN), a large private estates (PBS) and smallholders (PR). Village of Budi Asih, Sub District Banyuasin Pulau Rimau, Sumatera Selatan has the potential of âunused landâ for oil palm plantation development. This research purpose to analyze plantation invest by smallholder with sharing system between owner land and investor in Village of Budi Asih, Sub District Banyuasin Pulau Rimau, Sumatera Selatan .Besides taking into account the feasibility analysis of the aspects of non-financial (market aspects, technical, management and legal, economic and social, environmental) and financial aspects, the changes that will happen also to be taken into account to anticipate the financial impact that occurs on exertion cultivation of this commodity in the form of changes in production value (TBS productivities;TBS prices) and variabel cost.